Field evaluation of cultural control strategies for managing fall armyworm (Spodoptera frugiperda) infestations on maize crops (Agriculture, Food, and Natural Resources Journal, 2025)
This study aims to proffer a solution by promoting minimal use of insecticides using good agronomic practices that suppress pest development. Field trials were conducted during four cropping seasons in 2021 and 2022 at Kpong, Ghana. The experiment was laid out in a split-plot design with cropping system as the main factor and planting date as a factor with four replications. Maize was planted with cowpea as the intercrop and was planted at two-week intervals each for three different dates to determine the effects of the factors in FAW infestation and damage on maize. The results revealed that planting dates did not influence the infestation of the pest in terms of larval population across all seasons (F (2, 12) = 1.27, P = 0.3150); however, the damage caused was significantly different, with maize planted late recording the highest damage. The cropping system shows its impact where maize planted solely recorded high infestation of FAW as well as a high level of damage across all seasons examined. Seasonal variation occurred in the total number of FAW larvae (P < 0.05) regardless of the factors, and this could be attributed to the prevailing rainfall pattern. However, the yield of maize was not influenced by the cropping system or planting date across seasons. Parasitoids of FAW, including T. remus, Ch. bifoveolatus, and Coccygidium luteum, were observed, with Coccygidium luteum recording the highest abundance (71.43%). The findings in this study have shown the potential of cultural strategies as a sustainable means of fall armyworm management.